Optimal tilt magnitude determination for aberration-corrected super resolution exit wave function reconstruction. - Haigh, S; Sawada, H; Kirkland, A (2009)
Transmission electron microscope (TEM) images recorded under tilted illumination conditions transfer higher spatial frequencies than axial images. This super resolution information transfer is highly directional in a single image, but can be extended in all directions through the use of complementary beam tilts during exit wave function reconstruction. We have determined the optimal experimental tilt magnitude for aperture synthesis in an aberration-corrected TEM. It is shown that electron-optical aberration correction allows the use of larger tilt angles and reduces the constraints that are imposed on experimental data acquisition in an uncorrected microscope. We demonstrate that, in many cases, the resolution improvement achievable is now limited by the sample and not by instrumental parameters. An exit wave function is presented that has been successfully reconstructed from a dataset of aberration-corrected images, including images acquired at a beam tilt of 18 mrad, which clearly demonstrates a resolution improvement from 0.11 nm to better than 0.08 nm at 200 kV.